MARCIN ŚWIETLICKI – POETA KANONICZNY? - Panas, Paweł (Colloquia Litteraria, 2016)
Establishing the canon of literary works created after 1989 remains an open question. We still lack a comprehensive, axiologically oriented picture of Polish literature of the turn of the centuries. The case of Marcin Świetlicki’s poetry seems a particularly compelling issue in this context. His poetry is popular and continues to enjoy wide readership as well as it receives extensive appreciation among literary critics. At the same time one can effortlessly find in Świetlicki’s works expressive poetic gestures aiming at highlighting its distinctiveness, consciously undermining the possibility of accord between a community and an individual. In the face of this paradox the identity of the experience of modernity proves to be the crucial element which establishes and conditions the basic pact concluded by the poet with his readers.